Comparative analysis of the influence of heating and cooling on concrete strength (Research, Society and Development, 2019)
The elaboration of this article occurred after a research in which the comparative analysis of the influence of heating and cooling on concrete strength was studied. For this, tests were carried out in the laboratory, in addition to the concreting of the concrete in concrete mixer, where it was observed that the use of the trace of the material mentioned above, refers to the characteristic resistance of the compression of 25 Mpa. The research also made a comparative study between natural concrete and another that was exposed to high temperatures, in a gas furnace and soon after removed, subjected to a cooling with water, whose objective is to analyze the control and qualification of this concrete. As previously stated, the tests were all done in the laboratory in order to demonstrate the influence at high temperatures and in its instantaneous drop, where a trace of concrete was executed, that shaped 25 specimens of which twelve were made to prove if the trace contains the required characteristic resistance. As the tests were carried out after seven days, twenty-one days and twenty-eight days, it was observed that in all of them, the concrete did not gain resistance, but lost much of it, reaching a reduction of 66.74%. This draws attention to the importance of being aware of the material and its behavior, since a fire in structures such as those analyzed can lead to massive cases of death and material loss. Therefore, it is extremely important to make such an assessment, to avoid possible tragedies.